Urban Emissions and Regional Air Quality in India - Karambelas, Alexandra (Proceedings of the Wisconsin Space Conference, 2017)
Satellite observations from the Ozone Monitoring Instrument are used in support of model evaluation of seasonal average results from the U.S. Environmental Protection Agency (EPA) Community Multi-scale Air Quality (CMAQ) model. Model evaluation was conducted with the purpose of identifying regional biases in model output compared to tropospheric columns. Comparison with tropospheric column NO2, an anthropogenic indicator, reveal that there are uncertainties regarding the emissions inventory input to CMAQ. Results have implications for developing accurate model inputs to produce accurate model output for relevant health impact assessments, which are increasingly important with increasing population, urbanization, and pollution in the region.